Implementasi Metode VIKOR Penentuan Calon Penerima Program Indonesia Pintar - Emi Okta Purwita Sari; Yessica Siagian; Edi Kurniawan (LPPM STMIK Royal Kisaran, 2022)
Abstract: SMPN 2 Aek Ledong is a junior high school in Aek Bange Village, Aek Ledong District, Asahan Regency. Some of the people of Aek Bange Village are classified as middle to lower economic status, for that the school implements the Smart Indonesia Program for underprivileged students. The selection of prospective students receiving the Smart Indonesia Program in the first stage has been using the Microsoft Excel application which is used in a simple way, but there are many criteria that must be taken into account, so that it is difficult to determine prospective students who receive PIP in the first stage, to overcome these problems a system is needed. decision support that assists in determining the prospective recipients of the Smart Indonesia Program using the VIKOR method. The goal is to facilitate administrative activities in determining prospective PIP recipients quickly and on target. The VIKOR method focuses on ranking and selecting from a set of alternatives, and determining a compromise solution to the problem of conflicting criteria. The ranking results from the student list sample data in 2021 obtained the largest value to the smallest value, but the ranking results with the smallest value which is the best rank, in this study maximizes the ranking value results, namely from a value of 0 to 0.643 which is the best rank. Keyword: decision support system; student; PIP; VIKOR; Abstrak: SMPN 2 Aek Ledong merupakan sekolah menengah pertama di Desa Aek Bange, Kecamatan Aek Ledong, Kabupaten Asahan. Sebagian masyarakat Desa Aek Bange status perekonomiannya tergolong menengah kebawah, untuk itu pihak sekolah menerapkan Program Indonesia Pintar bagi siswa-siswi yang kurang mampu. Penyeleksian calon siswa penerima Program Indonesia Pintar pada tahap pertama selama ini menggunakan aplikasi microsoft excel yang dimanfaatkan dengan cara yang sederhana, namun banyaknya kriteria-kriteria yang harus diperhitungkan, sehingga kesulitan dalam penentuan calon siswa penerima PIP pada tahap pertama, untuk mengatasi permasalahan tersebut diperlukan sistem pendukung keputusan yang membantu dalam penentuan calon penerima Program Indonesia Pintar dengan metode VIKOR. Tujuannya dapat mempermudah aktivitas tata usaha dalam menentukan calon penerima PIP secara cepat dan tepat sasaran. Metode VIKOR berfokus pada perangkingan dan memilih dari satu set alternatif, dan menentukan solusi kompromi untuk masalah kriteria yang bertentangan. Hasil perangkingan dari data sample daftar peserta didik pada tahun 2021 didapat nilai terbesar hingga nilai terkecil, namun hasil perangkingan dengan nilai terkecil yang merupakan peringkat terbaik, dalam penelitian ini memaksimalkan hasil nilai perngkingan, yaitu dari nilai 0 sampai dengan nilai 0,643 yang merupakan peringkat terbaik. Kata Kunci : sistem pendukung keputusan; siswa; PIP; VIKOR